MENINGKATKAN KOMPETENSI GURU DALAM PENYUSUNAN RPP YANG BAIK DAN BENAR MELALUI PENDAMPINGAN BERBASIS MGMP SEMESTER SATU TAHUN 2015/2016 DI SMP NEGERI 16 MATARAM - Mukhammad Nazuhi (Valid: Jurnal Ilmiah, 2016)
The background of this study is the low competence of teachers targeted at SMPN 16 Mataram in the preparation Pelakssanaan Plan (RPP) is good and right that impact less confident in the learning process. The solution was held mentoring both groups and individuals in the preparation of RPP is good and right. The goal is to determine the effectiveness of the MGMP-based assistance in the effort to improve the competence of teachers in preparing the RPP is good and right, which is beneficial to improve the professionalism as the principal and the teachers to enhance the learning process in the classroom. Hypothesis action: improving the competence of teachers of SMP target 16 Mataram half of the 2015/2016 school year in preparing the RPP is good and right. This study was conducted by two cycles, each cycle two meetings. Stages of each cycle is the planning, implementation, observation, and reflection. Indicators of success in this study are; 1) the observation of the principal and teacher observation during the process of mentoring has obtained an average score of> 4.0, 2) the work of teachers in the preparation of RPP achieve> 85% with an average value of> 80.00. Results of the study in the first cycle of observation Headmaster average (3.30), teacher observation average (3.40) and the work of individual average value (68.95) with the percentage of achievement (0%). In the second cycle of observation Headmaster average (4.30), teacher observation average (4.20) and the work of individual average value (85.43) with the percentage of achievement (100%). Indicators of success has been achieved, research in declared unsuccessful and was stopped in the second cycle. Conclusion; implementation of mentoring can improve teacher competence SMP target 16 Mataram in the preparation of RPP is good and right. It is recommended that the Principal others doing similar research in improving the competence of teachers, and the teachers of subjects in order to develop lesson plans properly